1994
DOI: 10.1111/j.1465-7287.1994.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Subsidies, Water Transfers, and Economic Efficiency

Abstract: Water pricing subsidies and restrictions on water transfers are integral features of federal water supply policies in the western United States. Critics claim that these features discourage efficient use of water. However, current analyses ignore an important feature of federal water supply contracts: entitlement ceilings. This paper analyzes the implications of entitlement ceilings for federal water policies and several proposals for policy reform, including eliminating transfer restrictions, reducing pricing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Since surface supplies are constrained, there has been debate over the extent to which surface water prices might influence quantity demanded by agricultural producers (Loomis, 1994;Kanazawa, 1994). The effect of higher surface water prices on deep percolation was also considered here.…”
Section: Discussionmentioning
confidence: 99%
“…Since surface supplies are constrained, there has been debate over the extent to which surface water prices might influence quantity demanded by agricultural producers (Loomis, 1994;Kanazawa, 1994). The effect of higher surface water prices on deep percolation was also considered here.…”
Section: Discussionmentioning
confidence: 99%
“…Effluent charges, effective in theory, are usually introduced to generate income for the water treatment utility in the public domain, which competes with the firms' innovations (Schuurman, 1988). Subsidies in the water management discourage innovations when available technologies from the past share in this support (Nentjes and Scholten, 1989;Kanazawa, 1994). Public-private policy arrangements in the form of covenants temper dissemination because various, often contrary, interests in water must be satisfied (Derksen and Krozer, 1996).…”
Section: Motives For and Barriers To Innovationsmentioning
confidence: 98%
“…Only a few studies, found in Category C in the previous analysis (Shultz & Soliz, ; Ojeda et al, ; Ortega‐Pacheco et al, ; Almendarez‐Hernández et al, ) have examined communities where water supply service is reliably available, but heavily subsidized. In many emerging economies, high subsidies contribute to dramatic overuse of water, and a concomitant disincentive to adopt more sustainable water management techniques (Bithas, ; Budds & McGranahan, ; Kanazawa, ; Kumar & Singh, ; Myers, ; Myers, ; Rosegrant & Cline, ). Contingent valuation surveys offer an excellent opportunity to measure how much consumers are actually willing to pay for potable water, with contextual information provided about the environmental impact.…”
Section: The Future: Pontential Pathways For Contingent Valuation Stumentioning
confidence: 99%